A Thermodynamic Model for the Solubility of SO2 in Multi-Ion Electrolyte Solutions and Its Applications - Baoyi Feng; Zequn Zhang; Mei Xu; Shide Mao (Applied Sciences)
A solubility model of SO2 in multi-ion electrolyte solutions has been developed by the activity-fugacity relation at vapor-liquid equilibria. The fugacity coefficient of SO2 in the vapor phase is calculated by the equation of state (EOS) of pure SO2, and the activity coefficient of SO2 in the liquid phase is calculated by the Pitzer activity coefficient theory. The model can reproduce the reliable solubility data of SO2 in pure water and multi-ion electrolyte solutions (Na+, K+, Cl−, <semantics><msubsup>SO42−</msubsup></semantics>) within or close to experimental uncertainties. Although the second-order and third-order interaction parameters between SO2 and Mg2+ and Ca2+ have been adopted by an approximation, the solubility model can also be extended to predict the SO2 solubility in seawater. In addition, combining with the EOS of a CO2-SO2 fluid mixture, the model can be used to predict the solubility of a CO2-SO2 mixture in aqueous electrolyte solutions. The calculated results are consistent with experimental data, which indicates that the solubility model has certain predictive ability.